The Relationship Of The UN Security Council With The International Criminal Court In The Light Of The Rome Statute (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The international community has suffered many international crimes ,  where are war crimes , genocide and crimes against humanity have become a major obstacle facing the conscience and values of humanity , The first and second world wars witnessed a criminal environment in which crimes of great gravity were committed against humanity , and the temporary courts that were established by decision from the UN Security Council , based on its powers stipulated in Chapter VII , paved the way for the establishment of the International Criminal Court as a permanent international judicial body governed by the Rome Statute as a result of its failure to achieve criminal justiceIt should be noted that the issue of the relationship between the UN Security Coucil and  the International Criminal Court occupied a wide area of discussion during the Preparatory Committees for the establishment of the Criminal CourtDue to the different nature of the work of the United Nations Security Coucil , as it is considered  a political organ concerned with political matters in the international community , while the International Criminal Court is an independent judicial organ from the United Nations , despite that the UN Security Council was granted broad powers under the Rome Statute Basically based on the Charter of the United NationsAuthorizing  the Security Council to take measures that it deems appropriate to maintain international peace and security , especially that the crimes that the International Criminal Court is concerned with may constitute the greatest threat to international peace and security this calls for the intervention of the UN Security Council , The relationship between the UN Security Council and the International Criminal Court is nothing but an extension of its powers under Chapter VII of the Charter of the United Nations , There is no doubt that these broad powers have sparked controversy over the effects of these powers on the court’s mechanism of work.Will the Security Council , which is a political organ , have a positive role that contribubutes to activating the court’s activity in prosecuting the perpetrators of  international  crimes , or will it have a negative role that disrupts the work of the court ?